Experimental and computational analysis of abnormal grain growth. (October 2015) - Pimentel, G.; Toda-Caraballo, I.; Capdevila, C.
Abstract : The mechanisms involved in the abnormal grain growth of the iron based oxide dispersion strengthened alloys are analysed in the present work. Its microstructural evolution takes place at high temperatures (0.9 T m ) and is characterised by an initial submicrometre size microstructure and a strong < 110>|| rolling direction (RD) texture that evolves into a few extremely coarse grains (mm sizes) with < 112>||RD orientation. The analysis of the observed grain boundaries has been completed by molecular dynamics simulations. Microstructure evolution consists of an extended recovery process, followed by an abnormal grain growth stage, consequence of the orientation pinning mechanism and the proximity to a symmetric tilt boundary family between the < 110>||RD and < 112>||RD grains.